Implementasi Nilai-Nilai Pancasila Pada Sila Ke 5 Oleh Pegawai Di Kantor Urusan Agama Medan Johor - Muhammad Zuhri, Muftia Jannah, Arif Prabowo, Elma Sari Pane, Khairani (ALACRITY : Journal of Education, 2022)
Pancasila, which is the basis of the Republic of Indonesia, certainly has values ??that uphold the spirit of the state and also a sense of love for the Indonesian state. Looking at the five precepts of Pancasila, there is one principle that really upholds the value of diversity and togetherness, namely the fifth principle which reads "Social Justice for All Indonesian People". This study uses qualitative research methods using interviews and also looking at the field conditions and the purpose of this study is to discuss the values ??of the 5th precepts of Pancasila at the Medan Johor Religious Affairs Office. The Office of Religious Affairs which is of course used by all religions without exception of course must have the values ??of justice because of course people will come to KUA to resolve religious cases not only about marriage, so KUA is obliged to use the philosophy of the fifth precept so that there is harmony and also justice for the community while at the KUA